Efektivitas Pengajaran Roh Kudus dalam Pendidikan Agama Kristen sebagai Upaya Pembentukan Moralitas Siswa - Suryadi, Suryadi; Dotrimensi, Dotrimensi (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
The decline of students' morality is one of the educational challenges that requires serious attention, especially in character formation through Christian Religious Education. This study aims to analyze the influence of learning the content of Christian Religious Education, especially material on the Holy Spirit, on the morality of Christian students at SMAN 3 Palangka Raya. The research uses a quantitative approach with a correlational descriptive method. The results showed that the learning of PAK content was in the category of quite good, while the morality of students was in the category of very good. PAK learning has been proven to have a significant effect on student morality with a contribution of 17.5%. Among the indicators studied, the Holy Spirit material made the most dominant contribution to improving students' morality. In addition, there was no difference in perception of PAK learning based on gender, but the morality of female students was significantly higher than that of male students. This study concludes that learning about the Holy Spirit in PAK plays a positive role in the formation of students' morality.